Thermogenic responses in Eurasian Tree Sparrow (Passer montanus) to seasonal acclimatization and temperature-photoperiod acclimation - Lin Li; Jingru Ge; Sangyu Zheng; Lihong Hong; Xini Zhang; Ming Li; Jinsong Liu (Avian Research, 2020)
Abstract Background Small birds in temperate habitats must either migrate, or adjust aspects of their morphology, physiology and behavior to cope with seasonal change in temperature and photoperiod. It is, however, difficult to accurately measure how seasonal changes in temperature and photoperiod affect physiological processes such as basal metabolic rate (BMR) and metabolic activity. To address this problem, we collected data in each month of the year on body mass (M b) and BMR, and conducted a series of experiments to determine the effect of temperature and photoperiod on M b, BMR and physiological markers of metabolic activity, in the Eurasian Tree Sparrow (Passer montanus). Methods In one experiment, we measured monthly change in M b and BMR in a captive group of birds over a year. In another experiment, we examined the effects of acclimating birds to two different temperatures, 10 and 30 °C, and a long and a short photoperiod (16 h light:8 h dark and 8 h light:16 h dark, respectively) for 4 weeks. Results We found that these treatments induced sparrows to adjust their M b and metabolic rate processes. Acclimation to 30 °C for 4 weeks significantly decreased sparrows’ M b, BMR, and energy intake, including both gross energy intake and digestible energy intake, compared to birds acclimated to 10 °C. The dry mass of the liver, kidneys and digestive tract of birds acclimated to 30 °C also significantly decreased, although their heart and skeletal muscle mass did not change significantly relative to those acclimated to 10 °C. Birds acclimated to 30 °C also had lower mitochondrial state-4 respiration (S4R) and cytochrome c oxidase (COX) activity in their liver and skeletal muscle, compared to those acclimated to 10 °C. Birds acclimated to the long photoperiod also had lower mitochondrial S4R and COX activity in their liver, compared to those acclimated to the short photoperiod. Conclusions These results illustrate the changes in morphology, physiology, and enzyme activity induced by seasonal change in temperature and photoperiod in a small temperate passerine. Both temperature and photoperiod probably have a strong effect on seasonal variation in metabolic heat production in small birds in temperate regions. The effect of temperature is, however, stronger than that of photoperiod.